The Effect of Tax Avoidance And Leverage On Profitability In Sub-Sector Companies (Property, Real Estate And Building Construction) Registered On The Idx 2020-2023 - Putri Annisa; Jhon Piter; Tetty Tiurma Uli Sipahutar (International Journal of Science and Environment (IJSE), 2025)
This study was conducted to gain a better understanding of how tax avoidance and leverage affect the profitability of real estate and building construction sub-sector companies listed on the IDX from 2020 to 2023. A quantitative method based on multiple linear regression analysis was used in this work. The researcher compiled a sample of 36 companies with 144 observations using secondary data obtained from the IDX website. The sample was intended to represent the real estate property and building development industry and comprised of financial statements from 92 companies. There was no significant effect of ETR or DER on ROA, either alone or in combination, according to the results of this study. This is due to factors related to companies not fully implementing a strategy for balanced tax and leverage. This is in line with concerns voiced by those in the know.